Cardiomyocyte infection by Trypanosoma cruzi promotes innate immune response and glycolysis activation - Venturini, Gabriela; Alvim, Juliana M.; Padilha, Kallyandra; Toepfer, Christopher N.; Gorham, Joshua M.; Wasson, Lauren K.; Biagi, Diogo; Schenkman, Sergio; Carvalho, Valdemir M.; Salgueiro, Jessica S.; Cardozo, Karina H. M.; Krieger, Jose E.; et al. (Frontiers in Cellular and Infection Microbiology, 2023)
Introduction Chagas cardiomyopathy, a disease caused by Trypanosoma cruzi (T. cruzi) infection, is a major contributor to heart failure in Latin America. There are significant gaps in our understanding of the mechanism for infection of human cardiomyocytes, the pathways activated during the acute phase of the disease, and the molecular changes that lead to the progression of cardiomyopathy. Methods To investigate the effects of T. cruzi on human cardiomyocytes during infection, we infected induced pluripotent stem cell-derived cardiomyocytes (iPSC-CM) with the parasite and analyzed cellular, molecular, and metabolic responses at 3 hours, 24 hours, and 48 hours post infection (hpi) using transcriptomics (RNAseq), proteomics (LC-MS), and metabolomics (GC-MS and Seahorse) analyses. Results Analyses of multiomic data revealed that cardiomyocyte infection caused a rapid increase in genes and proteins related to activation innate and adaptive immune systems and pathways, including alpha and gamma interferons, HIF-1α signaling, and glycolysis. These responses resemble prototypic responses observed in pathogen-activated immune cells. Infection also caused an activation of glycolysis that was dependent on HIF-1α signaling. Using gene editing and pharmacological inhibitors, we found that T. cruzi uptake was mediated in part by the glucose-facilitated transporter GLUT4 and that the attenuation of glycolysis, HIF-1α activation, or GLUT4 expression decreased T. cruzi infection. In contrast, pre-activation of pro-inflammatory immune responses with LPS resulted in increased infection rates. Conclusion These findings suggest that T. cruzi exploits a HIF-1α-dependent, cardiomyocyte-intrinsic stress-response activation of glycolysis to promote intracellular infection and replication. These chronic immuno-metabolic responses by cardiomyocytes promote dysfunction, cell death, and the emergence of cardiomyopathy.